Zero point survey: a multidisciplinary idea to STEP UP resuscitation effectiveness - Cliff Reid; Peter Brindley; Chris Hicks; Simon Carley; Clare Richmond; Michael Lauria; Scott Weingart (Clinical and Experimental Emergency Medicine, 2018)
The primary survey assessment is a cornerstone of resuscitation processes. The name itself implies that it is the first step in resuscitation. In this article, we argue that in an organized resuscitation the primary survey must be preceded by a series of steps to optimize safety and performance and set the stage for the execution of expert team behavior. Even in the most time critical situations, an effective team will optimize the environment, perform self-assessments of personal readiness and participate in a preemptive team brief. We call these processes the ‘zero point survey’ as it precedes the primary survey. This paper explains the rationale for the zero point survey and describes a structured approach designed to be suitable for all resuscitation situations.